Transcriptomic analysis of cobalt stress in the marine yeast Debaryomyces hansenii - Gumá-Cintrón, Yariela (FEMS Yeast Res, 2015)
The yeast Debaryomyces hansenii overproduces riboflavin upon exposure to subtoxic levels of cobalt (Co(+2)). However, mechanisms for survival have yet to be studied and have been hindered by D. hansenii's high genetic heterogeneity among strains. In this study, we used transcriptomic analyses and RNA-seq in order to identify differentially expressed genes in D. hansenii in response to cobalt exposure. Highly upregulated genes under this condition were identified to primarily comprise DNA damage and repair genes, oxidative stress response genes, and genes for cell wall integrity and growth. The main response of D. hansenii to heavy metal stress is the activation of non-enzymatic oxidative stress response mechanisms and control of biological production of reactive oxygen species. Our results indicate that D. hansenii does not seem to be pre-adapted to survive high concentrations of heavy metals. These organisms appear to possess genetic survival and detoxification mechanisms that enable the cells to recover from heavy metal stress.